Progression of cardiovascular autonomic dysfunction in Holmes–Adie syndrome. Issue 9 (18th June 2010) - Guaraldi, P; Mathias, C J
Abstract : The Holmes–Adie Syndrome (HAS) is a disorder of unknown aetiology comprising unilateral or bilateral tonic pupils with near light dissociation and tendon areflexia. Although considered to be benign, troublesome symptoms may result from autonomic disturbances, affecting vasomotor, sudomotor and respiratory function. It is unclear if the autonomic manifestations of the disease remain stable or progress, as longitudinal studies with detailed autonomic assessments have not been described. The authors report four HAS patients studied at intervals over 16, 8, 4 and 2 years with cardiovascular autonomic tests (head-up tilt, isometric exercise, mental arithmetic, cutaneous cold, deep breathing, Valsalva manoeuvre and standing). In each, there was progression of cardiovascular autonomic deficits with time, accompanied by symptomatic worsening. These observations in HAS, for the first time, indicate progression of cardiovascular autonomic dysfunction of clinical significance. This has a number of implications, including those relating to aetiology and prognosis. The authors recommend regular clinical and laboratory follow-up, especially of cardiovascular autonomic function, in patients with HAS.